KERAGAMAN GENDER DAN NILAI PERUSAHAAN DI INDONESIA DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Krisyadi, Robby; Hendi, Hendi; Meilisa, Jennifer (KEUNIS, 2024)
Companies that have high company values tend to increase level of investor confidence in the progress and development of the company. Fluctuations in firm value in banking and insurance sector are the focus of the problem in this study. The objective of this study is to examine the moderating role of company size between gender on firm value on Indonesia Stock Exchange in banking and insurance sectors in 2018-2022. This method uses purposive sampling to collect data samples. There are 58 companies from the banking and insurance sectors as samples in this study. The data were analyzed using descriptive statistical methods and outlier tests with SDR using IBM SPSS Statistics 25 as well as convergent validity tests, discriminant validity tests, collinearity model tests, structural model tests, and hypothesis testing using SmartPLS 3.0. The results of the study (1) firm value is significantly positively affected by gender diversity; (2) firm size does not play a role in moderating the relationship between gender diversity and firm value.